Kegiatan Pengabdian Masyarakat mengenai Efektivitas Adukasi Berbasis Video di Media Sosial dalam Peningkatan Pengetahuan terhadap Stress Akademik Mahasiswa - Dewi Kusumangningsih; Nazwa Latifah; Tria Amelisa; Helen Eka Maharani; Risma Widia Agustina; Febiyola Kurnia; Intan Nur Arsyi R; Rani Putri A; Vera Dwi Mulyani; Rani Andesda; Yusra Yusra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Academic stress is a prevalent issue among Indonesian students, affecting both their academic performance and mental well-being. This study investigates the effectiveness of short educational videos on social media in improving students' knowledge about academic stress. A descriptive quantitative approach was used, with a sample of 35 Nursing students from the 2024 cohort at Malahayati University. The data was collected through questionnaires administered before and after students were exposed to 1-3 minute educational videos. The results showed a notable increase in the average knowledge score, from 82.71 to 85. The findings suggest that short videos, which are visually engaging and easy to access, are highly effective for Generation Z learners. Social media platforms, particularly TikTok and Instagram, can be valuable tools for early psychological intervention, providing students with accessible resources to manage academic stress on their own. This study highlights the potential of leveraging digital platforms to support student well-being and offers insights into innovative approaches for addressing mental health challenges in educational settings.